ANALISIS PENGARUH METODE MENGHAFAL KELAS X.2 DAN DISKUSI KELAS X.5 TERHADAP PENINGKATAN HASIL BELAJAR SISWA MATA PELAJARAN BAHASA ARAB POKOK BAHASAN SUBYEK PREDIKAT( المُبْتَدَاُ وَالخَبَرُ ) SEMESTER GENAP DI SMA YASMIDA AMBARAWA PRINGSEWULAMPUNG : ANALISIS PENGARUH METODE MENGHAFAL KELAS X.2 DAN DISKUSI KELAS X.5 TERHADAP PENINGKATAN HASIL BELAJAR SISWA - Muhammad Thoha; Doni Sastrawan (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2018)
This study aims to describe the use of memorization and discussion methods in improving student learning outcomes in class X.2 and X.5 Yasmida Ambarawa High School. With the matter of subject- Predicate (المُبْتَدَأُ وَ الخَبَرُ) Thus the hypothesis of this study is the influence of the use of these methods to improve student learning outcomes. This research is a field research (Class Action Research) that is analyzing the effect of student learning outcomes in class X.2 using memorization methods and class X.5 using discussion methods. This research uses quantitative and qualitative data collection techniques. Qualitative data are taken from: student observations, student memorization data, observations of student activities, and teacher / teacher activities (APKG). While quantitative are taken from: cognitive, affective, and psychomotor. From this study, it was concluded that teaching subject-Predicate lesson (المُبْتَدَأُ وَالخَبَرُ) by using memorization method had more effect on improving student learning outcomes, student learning outcomes using memorization methods were not affected by student activities, and using discussion methods, student activities affect the results of memorization in student learning.